A Distinct Sensitization Pattern Associated with Asthma and the Thymic Stromal Lymphopoietin (TSLP) Genotype - Hiroaki Iijima; Yoshiko Kaneko; Hideyasu Yamada; Yohei Yatagai; Hironori Masuko; Tohru Sakamoto; Takashi Naito; Tomomitsu Hirota; Mayumi Tamari; Satoshi Konno; Masaharu Nishimura; Emiko Noguchi; et al. (Allergology International, 2013)
Background: Atopy is a phenotypically heterogeneous condition, and the extent to which atopy accounts for asthma is controversial. In this study, we aimed to identify the presence of distinct sensitization patterns to common inhaled allergens and their association with asthma, allergic rhinitis and TSLP genotypes. Methods: We studied 1683 adults from Tsukuba, a city in central Japan and 297 adults from Kamishihoro, a cedar-free, birch-dominant town in northern Japan. Levels of total serum IgE and specific IgE antibodies towards 14 major inhaled allergens were measured. With the use of these measures, cluster analysis was applied to classify the subjects' sensitization patterns. We also examined the genetic effects of 2 TSLP functional SNPs on the development of each sensitization pattern. Results: In the Tsukuba study, cluster analysis identified four clusters, including "Dust mite dominant", "Multiple pollen", "Cedar dominant", and "Low reactivity". In the Kamishihoro study, "Dust mite dominant", "Multiple pollen" and "Low reactivity" clusters were also identified, but a "Cedar dominant" cluster was not formed. The association with asthma was strongest for the "Dust mite dominant" cluster in both the Tsukuba and the Kamishihoro studies. In never smokers, both SNPs were associated with the "Dust mite dominant" cluster (OR > 1.2). In contrast, in current or past smokers, these alleles were inversely associated with the "Multiple pollen" cluster (OR <0.5). Conclusions: Cluster analysis identified the presence of distinct sensitization patterns to common inhaled allergens. TSLP may cause asthma by promoting innate allergic responses to indoor allergens and this contribution is significantly modified by smoking.